(untitled) (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2026)
Hypertension in pregnancy, defined as blood pressure ≥140/90 mmHg after 20 weeks of gestation, is a significant condition that increases the risk of stunting in children by restricting blood flow and oxygen supply to the placenta. This condition can result in impaired fetal growth and other severe complications. Hence, early detection of hypertension in pregnant women is crucial to prevent pregnancy complications and reduce the risk of stunting. This community service program utilized instruments such as a sphygmomanometer, stethoscope, attendance sheet, and blood test result form. The activities were conducted door-to-door over two days, with one blood pressure measurement taken per participant. The procedure began with obtaining informed consent and recording attendance, followed by blood pressure measurement and brief education on hypertension prevention during pregnancy. Among the 7 pregnant women who participated, 5 (71.42%) were aged 20–35 years, while one was under 20 years and another over 35 years. Blood pressure measurements revealed that 6 participants (85.71%) had normal blood pressure, while 1 (14.29%) was classified as pre-hypertensive according to JNC-VIII guidelines. The hypertension screening in pregnant women in Alitta Village was successfully implemented by the 65th cohort of Unhas KKN-PK students, achieving the target of examining 7 participants. This program is expected to lower hypertension rates, prevent stunting, raise awareness about the importance of health checks, and improve maternal health outcomes. — Hipertensi, termasuk pada ibu hamil, merupakan kondisi tekanan darah ≥140/90 mmHg pada kehamilan ≥20 minggu yang dapat meningkatkan risiko stunting pada anak dengan menghambat aliran darah dan oksigen ke plasenta. Kondisi ini dapat menyebabkan pertumbuhan janin terhambat dan komplikasi serius lainnya. Oleh karena itu, upaya meningkatkan kesehatan ibu hamil melalui deteksi dini hipertensi menjadi penting untuk mencegah komplikasi kehamilan dan stunting pada anak. Program pengabdian masyarakat ini menggunakan alat ukur berupa spigmomanometer, stetoskop, lembar absensi, dan lembar hasil pemeriksaan darah. Kegiatan dilaksanakan secara door to door selama dua hari dengan satu kali pengukuran per sampel. Proses dimulai dengan informed consent dan pengisian absensi, diikuti pengukuran tekanan darah dan pemberian edukasi singkat terkait pencegahan hipertensi selama kehamilan. Dari 7 ibu hamil yang berpartisipasi, 5 orang (71.42%) berusia 20-35 tahun, sedangkan masing-masing satu orang berusia di bawah 20 tahun dan di atas 35 tahun. Pengukuran tekanan darah menunjukkan hasil 6 orang (85.71%) normal dan 1 orang (14.29%) pra-hipertensi berdasarkan klasifikasi JNC-VIII. Screening hipertensi pada ibu hamil di Desa Alitta telah berhasil dilakukan oleh mahasiswa KKN-PK Unhas angkatan ke-65, mencapai target dengan memeriksa 7 ibu hamil. Program ini berhasil secara teknis dan telah mencapai target dengan memeriksa 7 orang ibu hamil, serta program ini menekan angka kejadian hipertensi dan pencegahan stunting serta meningkatkan kesadaran masyarakat akan pentingnya pemeriksaan kesehatan di Desa Alitta.